Research, writing, and publication initiative for medical and health science students - N Shah, Jay (Journal of Chitwan Medical College, 2026)
The integration of research methodology and scientific writing into undergraduate medical education is essential for developing physician-scientists responsive to community needs. The Undergraduate Research Writing and Publication (UGRWP) initiative marks a strategic shift from elective participation to structured, mandatory training in Nepal. This editorial outlines the UGRWP framework, which bridges the gap between theory and scholarship through scientific writing mastery, reference management, and ethical training. By institutionalizing this model at Patan Academy of Health Sciences (PAHS), which has been incorporated into undergraduates teaching learning at Chitwan Medical College (CMC), the program addresses systemic barriers such as lack of time and mentorship. Furthermore, it explores the future role of artificial intelligence and global metrics, ensuring graduates remain socially accountable while contributing to the global scientific community.